Structural Vibration Analysis of Historical Drum Tower Structure Caused by Underground Train Running - Zhou, Yefei; Bai, Xiaoxiao; Wang, Shengnian; Zhao, Kai; Su, Hui; Wang, Haiyan (Frontiers in Earth Science, 2022)
The vibration induced by underground metro operation could have significant impacts on the safety of building structures. In this study, the dynamic response of the Nanjing Drum Tower affected by the metro line four operation was investigated by a three-dimensional FEM coupling train-track-tunnel-foundation-soil-basement–Drum Tower model performed on a 64 CPU parallel computing cluster platform. The results show that the vertical vibration caused by the subway operation has a more serious impact on the historical structure of the Drum Tower than the horizontal vibration. The vertical vibration attenuates rapidly from the basement bottom to the top of the tower. The horizontal vibration amplifies along the height of the historical building. The truss roof significantly weakens the vibration. As the speed of the train increases, the amplitude of horizontal and vertical vibration increases gradually from the bottom to the roof of the Drum Tower despite a relatively smaller increase for the horizontal vibration. As for the double-track operation case, the vertical vibration amplitude is much greater than that for the single-track operation, and no significant difference is observed in the horizontal direction. The amplitudes of horizontal vibration velocity for the basement and Drum Tower are 0.131 and 0.060 mm/s, respectively.